2022
DOI: 10.1186/s12879-021-06964-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of Gram-negative and Gram-positive bacterial infection in acute cholangitis: a retrospective observational study

Abstract: Background To investigate the difference in the severity of illness, organ dysfunction, and prognosis of acute cholangitis due to different pathogenic bacterial infection types. Methods A retrospective observational study was performed. Patients who met the selection criteria according to blood culture and bile culture results of different pathogenic bacterial were divided into groups. The severity of illness, organ dysfunction, and prognosis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…ESBL is the most frequently single isolate in bile cultures in patients with cholangitis 15 . In contrast, enterococcus has been shown to be more common in patients with prior stenting and bacteremia, and cholangitis mortality is as high as 7.3 times higher than mortality diagnosed with polymicrobial blood infections 24,25 . Although shown in a surgical setting, 14 additional coded resistant infections were not significant for higher mortality in our post hoc analysis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…ESBL is the most frequently single isolate in bile cultures in patients with cholangitis 15 . In contrast, enterococcus has been shown to be more common in patients with prior stenting and bacteremia, and cholangitis mortality is as high as 7.3 times higher than mortality diagnosed with polymicrobial blood infections 24,25 . Although shown in a surgical setting, 14 additional coded resistant infections were not significant for higher mortality in our post hoc analysis.…”
Section: Discussionmentioning
confidence: 53%
“…15 In contrast, enterococcus has been shown to be more common in patients with prior stenting and bacteremia, and cholangitis mortality is as high as 7.3 times higher than mortality diagnosed with polymicrobial blood infections. 24,25 Although shown in a surgical setting, 14 additional coded resistant infections were not significant for higher mortality in our post hoc analysis. However, in our sub-analysis, we confirm more VRE and MDRO were associated with biliary stenting (Supplemental Table 3, Supplemental Digital Content 3, http://links.lww.com/JCG/A978), whereas slightly more ESBL were associated with biliary stone removal.…”
Section: Discussionmentioning
confidence: 54%
“…All 1570 inpatients with acute cholangitis admitted to the First Affiliated Hospital of Chongqing Medical University from July 2013 to January 2022 were considered for being preliminary included, the inclusion and exclusion criteria and case identification refer to our previous study, 13 as shown in Figure 1 . Taking into account some irresistible factors, as detailed in our previous study, 14 503 patients were eventually included.…”
Section: Methodsmentioning
confidence: 99%
“…For inclusion and exclusion criteria refer to our previous studies. 18 The inclusion criteria for acute cholangitis and the identification of cases are shown in Figure 1 The following factors prior to hospitalization were also taken into account: infection-related risk factors, whether CRE infection was detected before being hospitalized, pre-admission factors included hospitalization within 3 months (emergency admission, duration of emergency stay, use of carbapenems within 3 months prior to admission, and presence of infection before admission), whether or not a ventilator or artificial airway were used within a month prior to infection, whether the catheter was indwelled, whether the blood flow catheter was indwelled, catching infection previously, whether the patients were admitted to the intensive care unit (ICU), usage of antibacterial drugs, that is, combination of drugs, use of carbapenems, cephalosporins, tetracycline, fluoroquinolones, aminoglycosides, glycopeptides, sulfamides, and other antibacterial drugs, and their hours of use.…”
Section: Methodsmentioning
confidence: 99%
“…For inclusion and exclusion criteria refer to our previous studies. 18 The inclusion criteria for acute cholangitis and the identification of cases are shown in Figure 1 . In view of the following exclusion factors:) Bile culture and blood culture were not obtained, 2) Received treatment before admission, 3) Organ failure before onset, 4) Transfer to another hospital, and 5) Neither ERCP and surgical drainage were performed, 503 patients were finally included in this research.…”
Section: Methodsmentioning
confidence: 99%